Are threatened plant species specialists, or just more vulnerable to disturbance?. Issue 5 (2nd August 2014) - Monks, Adrian; Burrows, Larry; Wan, Shiqiang
Summary Many studies report an association between species rarity and/or threat status, and habitat specialization. However, specialization is often inferred from a species' narrow realized range and may be confounded with landscape disturbance history. We test whether threatened species are more specialized than non‐threatened plants using patterns of plant species turnover sampled at three occasions over 13 years in a lake shore ecosystem in Fiordland, New Zealand. If threatened plants are more specialized than non‐threatened plants, then we expect their rate of turnover to be higher than non‐threatened species in the same habitat across multiple time periods and changes to the disturbance gradient. The first sampling occasion (1997) was associated with high water levels and a low rate of change in maximum inundation period with elevation. The second two sampling occasions (2005 & 2010) were associated with periods of lower water levels and steep hydrological gradients. Changes along the disturbance gradient created by shifts in the hydrological regime were associated with a movement of threatened and non‐threatened plants downslope (up to 0·8 m in elevation) and a decline in overall cover over the 13 years of the study. Threatened species had higher rates of turnover in only the last of the three sampling periods, suggesting that threatened species were not more likely to be habitat specialists than non‐threatened species. Synthesis and applications. We suggest that threatened plant species are less resilient to disturbance than non‐threatened species and that these plants were slower to expand their range from the short‐term contraction caused by perturbation to the hydrological gradient. Disturbance history has implications for patterns of turnover more generally, and we suggest that species resilience may be a useful conceptual tool to identify species at risk of decline and inform pre‐emptive management action.